The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2024
DOI: 10.1590/0103-6440202405641
|View full text |Cite
|
Sign up to set email alerts
|

Preheated acid associated with silane and electric current in the adhesion of the resin cement to ceramic

Gustavo Belmiro Casaburi,
Marcos Henrique Ramos da Silva,
Lourenço Correr-Sobrinho
et al.

Abstract: This study verified the effect of the combination of preheated hydrofluoric acid/silane/electric current in the adhesion of the resin cement to ceramic. IPS E.max Press ceramic discs embedded in PVC rigid tubes were divided into four groups associating preheated hydrofluoric acid and silane applied with electrical current (n=10): Ha+S (Heated acid + silane); Ha+S+Ec (Heated acid + silane + electrical current); A+S (Acid + silane) and A+S+Ec (Acid + silano + electrical current). Resin cement/ceramic samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Adhesive fracture was predominant in all groups and evaluation moments. The Ha+S and A+S groups presented higher contact angle values compared to the Ha+S+Ec and A+S+Ec groups with lower values [7].…”
Section: Major Outcomesmentioning
confidence: 80%
See 3 more Smart Citations
“…Adhesive fracture was predominant in all groups and evaluation moments. The Ha+S and A+S groups presented higher contact angle values compared to the Ha+S+Ec and A+S+Ec groups with lower values [7].…”
Section: Major Outcomesmentioning
confidence: 80%
“…The composite resin to be used should be applied, choosing the appropriate material for each case [2,3]. Some work, analyzing the relevance of various chemical and mechanical treatments in old composite resins and repair bond strength, concluded that the improvement in the bond strength between the new and the old composite resin restoration requires increased harshness to institute micromechanical union between the surface of the old composite resin and the resin together [4,5].…”
Section: Major Outcomesmentioning
confidence: 99%
See 2 more Smart Citations